Efeito da auriculoterapia com laser em pessoas com dor crônica na coluna vertebral - ensaio clínico randomizado - Menezes, Flávia Da Silva (2020)
Pain is a symptom and one of the most frequent causes of seeking medical care. Among the chronic diseases, chronic pain in the spine can be highlighted, which have a negative impact on the quality of life of individuals. In this context, it is important to develop strategies aimed at pain control in the population, such as low-power Laser auriculotherapy. The aim of this study was to evaluate the effect of Laser auricular acupuncture on chronic spinal pain. This is a randomized controlled clinical trial in which volunteers underwent three evaluations, an pre-intervention; a post-intervention that was immediately after the end of the last intervention session and, 15 days after the end of treatment, denominated follow-up. The variables evaluated were instrument of characterization of the volunteer, pain intensity, nociceptive threshold in relation to mechanical stimulus, the greatest and least pain in the last seven days. In addition, the volunteers were divided into two groups using the Randomizer randomization software: control group (CG, n=23), which did not receive intervention, and experimental group (EG, n=24), which was submitted to 10 sessions of Laser ear acupuncture twice a week. The DCM 808 nm infrared low intensity (Therapy EC) Laser was used, with emission power of 100mW and a 4 Joules per point stimulated dosage. Then, for statistical analysis, the Statistical Package for the Social Sciences (SPSS) statistical program was used and the significance level adopted was 5%. The results showed that after the 10 sessions of auriculotherapy with Laser, there was a difference between the groups for the variables pain intensity, greater and lesser pain in the last seven days in the moments after intervention and follow up. There was a significant reduction in these three variables between the post and pre (p=<0.001) and follow up and pre (p=<0.001) moments for the EG. It was possible to observe that the EG showed clinical improvement, in relation to the variable pain intensity, between the pre and post (65,20%), pre and follow up moments (58,62%) when compared to the control group. For the nociceptive threshold, there was a significant increase in The EG between the pre and post intervention (p=0.017) and pre- and follow-up (p=0.016) moments. On the other hand, the CG showed a significant reduction in the nociceptive threshold between the pre- and post-intervention (p=0.001) and pre-and-follow-up (p=<0.001) moments. To conclude, the proposed intervention was effective in reducing pain intensity, as well as increasing the nociceptive threshold. The effects of the intervention remained in the follow-up 15 days after the last follow-up session with little change in the values of the variables evaluated.